Formation of the Intercultural Communicative Competence of Students in Process of Learning Foreign Languages - Mukharlyamova, Liliya; Konopleva, Natalya; Galimzyanova, Ilkhamiya; Berezhnaya, Irina (Journal of History Culture and Art Research, 2018)
The article is devoted to the problem of formation of the intercultural communicative competence of students in process of learning foreign languages. The urgent problem of vocational education is the preparation of students for the use of a foreign language in communicative and professional activities, as well as the formation of intercultural communication. Along with professional and communicative skills, a graduate of a university should know the cultural and social characteristics of other nationalities. It allows them to orientate themselves in repetitive sociocultural situations, make a dialogue with representatives of foreign cultures, seek and find ways to resolve interethnic and interconfessional conflicts and have such qualities as tolerance, openness and willingness to communicate. Formation of intercultural communicative competence among students implies awareness of the native culture and other cultures, their interrelationships; ability and readiness for communication prevent conflicts that inevitably arise from such contacts; the ability to build new patterns of behavior, based on the values and norms of different cultures.